Pemanfaatan Program Pemerintah Bantuan Langsung Tunai Di Desa Tambelang Kecamatan Maesaan Kabupaten Minahasa Selatan - Fidel S. Rumengan; Jenny Baroleh; Theodora M. Katiandagho (Sam Ratulangi University, 2022)
This study aims to determine the direct cash assistance (BLT) program is right on target in terms of accuracy of recipient recruitment, disbursement time, supervision and to determine community utilization of the BLT Program in Tambelang Village, Maesaan District. The research was carried out from January to February 2022. The data collected in the study were primary data obtained from direct interviews with BLT recipient communities using a questionnaire. Secondary data were obtained from the Tambelang Village Office, as well as data related to research taken from the internet. The number of BLT recipients was 130 respondents who received BLT phase I in 2021 and phase II in 2021. The sample selected by Purposive Sampling was 60 respondents. The results showed that the use of the government's direct cash assistance program in Tambelang Village was appropriate, the recipients of the assistance had fulfilled the correct recruitment process in accordance with the implementation instructions, on time in disbursing funds, officers disbursed aid funds according to the specified schedule. The Government's Cash Direct Assistance Program is used by the community to meet their daily basic needs, namely buying rice, eggs, meat, transportation and for emergency funds, namely buying medicine and children's school needs.